Psychological aspects of religious morality in middle and late adulthood - Tatala, Małgorzata (Kwartalnik Naukowy Fides et Ratio, 2021)
As a result of the study, the structure of religious morality including the following categories was distinguished: basis of moral functioning, moral attitude toward conflict situations, moral attitude toward experienced dissonances, and reference to the principle of moral autonomy. For the basis of moral functioning, the following subcategories were identified: Self, others, religion, consequences. For the moral attitude to conflict situations, the subcategories were: task-oriented, avoidant, emotional, religious. For the moral attitude toward experienced dissonances, the categories were: informational-religious, normative, avoidant, conflictual. With respect to the principle of moral autonomy, these were: congruence and incongruence. The participants of the study were 120 people of the Catholic faith, 60 each in middle and late adulthood. A Piagetian exploratory-critical interview was used, the design of which was based on Walesa’s model of religiosity. The frequency of specific subcategories of religious morality was significantly differentiated by the age of the subjects for the basis of moral functioning, moral attitude toward conflict situations, and moral attitude toward experienced dissonance. In late adulthood, religiosity serves an important function - especially in situations of conflict or events related to experienced moral dissonances.